Penguatan Kompetensi Menulis Artikel dan Mengelola Jurnal di Bidang Pendidikan bagi Guru Madrasah, SDI, dan SD di Kecamatan Kokop Kabupaten Bangkalan - Ali Nurhadi; Hilmi Qosim Mubah; Abdul Wafi (IAIN Madura, 2020)
The teacher is the spearhead of education because it deals directly with students during the learning process. The teacher also determines the direction of education in madrasahs and at schools. For this reason, it is necessary to strengthen the competence of madrasah teachers and teachers in schools to create superior, competitive, and prophetic madrasahs and schools. This article results from community engagement activities in the form of workshop on strengthening competency in writing and managing journals for teachers in madrasas and schools in Kokop - Bangkalan District. This article describes two research focuses, namely (1) How to improve teacher competence in writing scientific papers and publish them in journals at UPTD Pendidikan, Kokop Bangkalan District? (2) How to manage and develop an education journal in Kokop Bangkalan District? The results of this activity are: (a) Teachers potentially improve their self-competence in writing scientific papers and publish them in journals at UPTD Pendidikan, Kokop District, Bangkalan. (b) Teachers can manage and develop the education journal in Kokop Bangkalan District. (c) The offline-based education journal in Kokop sub-district can develop to become an online journal with the OJS (Open Journal System) platform.(Guru adalah ujung tombak pendidikan sebab berhubungan langsung dengan siswa saat proses pembelajaran berlangsung. Guru juga menentukan arah pendidikan di madrasah dan di sekolah. Untuk itu dibutuhkan penguatan kompetensi guru madrasah dan guru di sekolah dalam rangka mewujudkan madrasah dan sekolah unggul, kompetitif, dan berkarakter profetik. Artikel ini merupakan hasil dari kegiatan pengabdian kepada masayarakat dalam bentuk workshop penguatan kompetensi menulis dan mengelola jurnal bagi guru di madrasah dan sekolah di Kecamatan Kokop Bangkalan. Artikel ini memaparkan dua fokus penelitian yaitu (1) Bagaimanakah meningkatkan kompetensi guru dalam penulisan karya tulis ilmiah serta mempublikasinnya pada jurnal di UPTD Pendidikan Kecamatan Kokop, Kabupaten Bangkalan? (2) Bagaimanakah mengelola dan mengembangkan jurnal pendidikan di Kecamatan Kokop Kabupaten Bangkalan? Adapun hasil dari kegiatan ini berupa: (a) Para guru berpotensi meningkatkan kompetensi diri mereka dalam penulisan karya tulis ilmiah serta mempublikasinnya pada jurnal di UPTD Pendidikan Kecamatan Kokop Bangkalan. (b) Para guru dapat mengelola dan mengembangkan jurnal pendidikan di Kecamatan Kokop Bangkalan. (c) Jurnal pendidikan di Kecamatan Kokop yang berbasis luring berpeluang menjadi jurnal daring dengan platform OJS (Open Journal System)